Pengaruh Metode Penanganan Pascapanen Dan Suhu Simpan Terhadap Mutu Proksimat Dan Organoleptik Ikan Nike (Awaous melanocephalus) - Putalan, Reinal; Imran, Mohammad; Farid, Farid; Nusi, Fakhrunnisa; Mi'raz, Nurhawaliya; Ariany, Septian Palma (Jambura Fish Processing Journal, 2025)
Nike fish (Awaous melanocephalus) is a local fishery commodity with high nutritional value but limited shelf life due to its delicate physical characteristics. This study aimed to evaluate the effects of post-harvest handling methods and storage temperature variations on the proximate and organoleptic quality of nike fish. The research was conducted experimentally using a 2×3 factorial completely randomized design, consisting of two handling methods (conventional and hygienic) and three storage temperatures (room temperature ±28°C, cold storage ±4°C, and frozen storage ±−18°C). Proximate quality parameters analyzed included moisture, protein, fat, and ash content using AOAC methods, while organoleptic quality was assessed based on color, aroma, texture, and taste through a hedonic test by semi-trained panelists. The results showed that hygienic handling combined with frozen storage significantly maintained higher protein content and more stable moisture levels compared to other treatments. This combination also yielded the highest organoleptic scores across all sensory attributes. These findings indicate that hygienic handling and frozen storage are effective strategies for preserving the quality of nike fish during short-term storage. The results of this study can serve as a scientific basis for developing practical post-harvest handling protocols to support the strengthening of local fishery agribusiness systems.